Women of Asia
1 online resource (464 pages)
Keywords: With thirty-two original chapters reflecting cutting edge content throughout developed and developing Asia, Women of Asia: Globalization, Development, and Gender Equity is a comprehensive anthology that contributes significantly to understanding globalization’s transformative process and the resulting detrimental and beneficial consequences for women in the four major geographic regions of Asia—East Asia, Southeast Asia, South Asia, and Eurasia/Central Asia—as it gives "voice" to women and provides innovative ways through which salient understudied issues pertaining to Asian women’s situation are brought to the forefront.